Influence of Cabling on Photovoltaic System Performance: Wire Length, Diameter, and Material - Ebhota, Williams S.; Tabakov, Pavel (Kurdistan Journal of Applied Research, 2025)
Despite advancements in solar PV technology, significant challenges remain in the Global South, including financial, human resource, environmental, and technological constraints. System losses—caused by reflection, temperature effects, inverter inefficiency, cabling losses, shading, and degradation—are a major concern. This study examines how cabling parameters—wire length, diameter, and material—affect PV system performance and energy losses. Using a computational model, it evaluates a 3 kWp PV system in Durban, South Africa, analyzing efficiency, specific annual yield, and avoidable CO₂ emissions across various cabling configurations. The study’s key findings include: at a constant wire diameter of 4 mm, specific annual yield decreases as wire length increases, dropping from 977.36 kWh/kW at 5 m to 966.32 kWh/kW at 50 m, reflecting efficiency losses; at a constant wire length of 20 m, yield improves with increasing diameter, rising from 970.71 kWh/kWp at 2.5 mm to 977.81 kWh/kWp at 20 mm. Beyond 25 mm, yield gains diminish, stabilizing around 978.39 kWh/kW at 90 mm; at a fixed wire length of 20 m, avoided CO₂ emissions increase with wire diameter up to 25 mm, after which gains level off from 30 mm to 90 mm; at a constant diameter of 4 mm, avoided CO₂ emissions increase from 1,378 kg/year at a wire length of 5 m to 1,363 kg/year at 50 m. These findings highlight the importance of optimizing cabling parameters to minimize system losses and enhance the overall efficiency and sustainability of PV systems.